2019
DOI: 10.1177/0731684419868845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compaction roller on layup quality and defects formation in automated fiber placement

Abstract: Application of automated fiber placement is limited by defects formed in the prepreg tows during the layup process. An extensive experimental study is performed to investigate the effect of compaction roller on the quality of the layup. Five different compaction rollers with different stiffness and architectures were manufactured and employed to dispense prepreg tows at various process conditions. Layup quality was examined and different defects including tow buckling and blister were identified. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The compression force applied and controlled by the roller plays a vital role in the mechanical properties of tack and wrinkle formation. The compaction pressure distribution generated by roller on prepreg was investigated in [19,20], respectively. Besides, the compression force between the roller and tape and the guidance system leads to an initial defect in tape that affects the wrinkle formation.…”
Section: Methodsmentioning
confidence: 99%
“…The compression force applied and controlled by the roller plays a vital role in the mechanical properties of tack and wrinkle formation. The compaction pressure distribution generated by roller on prepreg was investigated in [19,20], respectively. Besides, the compression force between the roller and tape and the guidance system leads to an initial defect in tape that affects the wrinkle formation.…”
Section: Methodsmentioning
confidence: 99%
“…Two research centres have grown the field in recent years: The Chair of Carbon Composites at the Technical University of Munich (TUM) [12][13][14][15] and the Concordia Centre for Composites (CONCOM) [11,16,17]. The frameworks developed at the two institutions are similar in that they both take account of every constituent involved (i.e.…”
Section: Uob Confidentialmentioning
confidence: 99%
“…4,5 Compaction force is one of the most important process parameters for AFP, and many studies have shown that appropriate compaction force helps to improve prepreg tack levels and layup quality. [6][7][8][9][10][11] However, little attention has been paid to the compaction pressure (the force per unit area on prepreg layers, unit: Pa), which is more essential than compaction force (unit: N). At present, most of the researches on AFP process were carried out on flat mold, in which case the compaction pressure distribution is relatively even.…”
Section: Introductionmentioning
confidence: 99%